2020
DOI: 10.1007/s10493-020-00504-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of phytoseiid mites in Turkey based on the internal transcribed spacer (ITS) region, with a new record for the country

Abstract: The family Phytoseiidae contains many predatory mite species and some are used in biological control programs worldwide. The identification of phytoseiid mites is based on tiny morphological structures and sometimes species diagnosis is not easy especially for nontaxonomists. DNA-based approaches may offer a fast and accurate diagnosis to overcome these difficulties, nevertheless more DNA sequences are needed to determine intra-and inter-specific variations and to provide accurate decision rules based on genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…In the present study, the 28S nucleotide sequences showed that the two Neoseiulus species are different species as they formed separate clades. The ML tree also showed that the genus Neoseiulus appeared to be polyphyletic, which agrees with previous phylogenies based on the 12S rRNA genes of mtDNA (Tsolakis et al 2012) and the ITS region of nrDNA (Inak et al 2020). The current morphological and molecular analyses strengthen the taxonomic separation of the two species.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, the 28S nucleotide sequences showed that the two Neoseiulus species are different species as they formed separate clades. The ML tree also showed that the genus Neoseiulus appeared to be polyphyletic, which agrees with previous phylogenies based on the 12S rRNA genes of mtDNA (Tsolakis et al 2012) and the ITS region of nrDNA (Inak et al 2020). The current morphological and molecular analyses strengthen the taxonomic separation of the two species.…”
Section: Discussionsupporting
confidence: 88%
“…Our examinations of the current specimens show some differences when compared to the re-description by Inak et al (2020). For example, our specimens have a reticulated dorsal shield and three macrosetae on leg IV as opposed to a smooth dorsal shield and only one macroseta on leg IV in Inak et al (2020). The three macrosetae are clearly illustrated by Kolodochka (1978) whereas the reticulated dorsal shield was only simply illustrated by Beglyarov (1981) and is not included in the other re-descriptions (Wainstein, 1962;Arutunjan, 1977;Kolodochka, 1978;Miedema, 1987;Inak et al, 2020).…”
Section: Remarksmentioning
confidence: 61%
“…Legs (Figure 5 World Distribution. Denmark, Finland, France, Georgia, Germany, Hungary, Iran, Italy, Kazakhstan, Latvia, Moldova, Poland, Russia, Serbia, Slovakia, Slovenia, Ukraine (Demite et al, 2020), Turkey (Inak et al, 2020), and this study.…”
Section: Neoseiulus Reductus (Wainstein)mentioning
confidence: 77%
See 2 more Smart Citations